RATIONAL NUTRITION OF PREGNANT WOMEN IN THE PERIOD OF PRENATAL DEVELOPMENT OF THE FETUS - Abdullaeva Zamira Shamshaddinovna; Shikhnazarova Guzal Alisherovna; Kasimova Gulchekhra Karimullaevna; Akbarali Sattarov Baxtiyorovich (Web of Journals Publishing, 2023)
In prenatal development, several periods are conditionally distinguished, pre-implantation development, implantation, organogenesis and placentation, phegogenesis . Rational nutrition is one of the main conditions for a favorable course and outcome of pregnancy and the normal development of the fetus. During pregnancy, the woman's body's need for vitamins and minerals increases significantly, since all systems and organs of the expectant mother work in an enhanced mode to meet the needs of a developing child in utero. The recommended norms of physiological needs for basic nutrients and energy of women are presented.
Keywords: prenatal development of the fetus, rational nutrition, healthy food, nutrition for pregnant women, balanced diet.